Penyuluhan makanan bergizi seimbang pada anak-anak desa Golong selama new normal (fokus pada pendekatan metode ular tangga) - M. Thonthowi Jauhari; Nurul Hidayah (LPPM Universitas Bumigora, 2021)
The health issue is still a primary obstacle in Indonesia. All sectors need to pay attention to it; otherwise, the human resource level will be low. In line with this socialization is needed to encourage children especially, to start aware of consuming a healthy diet. In addition, this can broaden children’s horizons about what they better eat. The method in this activity is by using snake ladder game which is more attractive and fun for children. This method, in fact, can enhance children's knowledge. During the pre-test, the correct answers were 11,9 on average; while after the socialization the right answers were 14,5 on average. It shows that the sharing knowledge by snake ladder game is effectively helpful for children to increase their knowledge.